If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + 4x = 3(7x + -4) + 5x Reorder the terms: 10 + 4x = 3(-4 + 7x) + 5x 10 + 4x = (-4 * 3 + 7x * 3) + 5x 10 + 4x = (-12 + 21x) + 5x Combine like terms: 21x + 5x = 26x 10 + 4x = -12 + 26x Solving 10 + 4x = -12 + 26x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-26x' to each side of the equation. 10 + 4x + -26x = -12 + 26x + -26x Combine like terms: 4x + -26x = -22x 10 + -22x = -12 + 26x + -26x Combine like terms: 26x + -26x = 0 10 + -22x = -12 + 0 10 + -22x = -12 Add '-10' to each side of the equation. 10 + -10 + -22x = -12 + -10 Combine like terms: 10 + -10 = 0 0 + -22x = -12 + -10 -22x = -12 + -10 Combine like terms: -12 + -10 = -22 -22x = -22 Divide each side by '-22'. x = 1 Simplifying x = 1
| -21p^2-24p=12 | | (-x^5)(-x)= | | 10x+2=-2+4 | | 2kx*2kx=0 | | (3x+9)+(6x+7)= | | 5x+10=4x+15 | | 6x+10y+11=0 | | x^2+2kx-7=0 | | -10p+3(8+8n)=-6(n-4) | | 137-5x=-58-8x | | 5x+9=39-7x | | 3y(5y+9)=0 | | 63-6x=9+18 | | 5x-3(x-10)=100-2(3x+5) | | 2(g+6)=24 | | .83=-.4b+.33b | | 5(g+6)=24 | | 3(x^2+4x+4)=0 | | n+8m=d | | 30n=-5 | | x=42*7 | | 2x(x-1)=5(x+3) | | 2x^3-11x^2+22x-15=0 | | 5x+31=14x-92 | | 945000+x=10x | | X^3-2x^2+3x+4=0 | | 5x-3(x-2)=30-3(x+3) | | 0.2x^2-80x+2500=0 | | 2t=34 | | 19x-17=3(4x-13) | | E+5=25 | | 6x-11y=0 |